Lgr5 expression, cancer stem cells and pancreatic cancer: results from biological and computational analyses. (April 2015) - Andrikou, Kalliopi; Santoni, Matteo; Piva, Francesco; Bittoni, Alessandro; Lanese, Andrea; Pellei, Chiara; Conti, Alessandro; Loretelli, Cristian; Mandolesi, Alessandra; Giulietti, Matteo; Scarpelli, Marina; Principato, Giovanni; et al.
ABSTRACT : Aims: To determine the relationship between Lgr5 and other stemness markers and pathologic features in pancreatic ductal adenocarcinoma (PDAC) samples.Materials & methods: In 69 samples, Lgr5 was analyzed by qRT-PCR together with a panel of 29 genes. Bioinformatic analysis was carried out to identify a possible pathway regulating Lgr5 expression in PDAC.Results: Lgr5 expression was not associated with the expression of tested cancer stem cell markers. Moreover, it was not an independent predictor of survival neither at univariate analysis (p = 0.21) nor at multivariate analysis (p = 0.225).Conclusion: Based on the lack of correlation between Lgr5 and tested cancer stem cell markers, Lgr5 does not seem to be a potential stemness marker or prognostic factor in PDAC.